Optimization of Ionic Soil Stabilizer Dilution and Understanding the Mechanism in Red Clay Treatment - Xuesong Lu; Jin Luo; Meinan Wan (Advances in Civil Engineering)
Due to the insufficient understanding of the mechanism for soil strengthening by using Ionic Soil Stabilizer (ISS), the application of ISS in soil treatment is limited. In this paper, red clay samples were treated by using ISS and the effects were examined by the Atterberg test and uniaxial pressure test. In order to understand the mechanism, ISS dilution-based seepage test and ξ-potential test have been carried out. The results show that the ISS-Water mixture of 1 : 200 was the most effective ratio to reduce the plasticity index. The measurements indicate the thickness of the pair-electricity layer of adjacent clay layers and the repulsion force among soil particles is reduced, which in turn enhances the attraction force of the clay layers. This process strengthens the connection among the soil particles and thus increases the strength of the soil as detected by the experimental tests.